Analisis Kelayakan Usaha Produksi Biji Kopi Sangrai dan Jasa Penyangraian: Studi Kasus pada Java Sumedang Coffee - Thoriq, Ahmad; Sampurno, Rizky Mulya; Imaduddin, Luthfie Hafidz (Jurnal Tanaman Industri dan Penyegar, 2020)
The development of specialty coffee roasted beans business and coffee roasting services is currently quite rapid, but often that the business is not based on the feasibility analysis. This study aims to analyze the feasibility level of the production of specialty coffee roasted beans and roasting service of coffee beans. This study was carried out beginning from November 2019 until February 2020 with case study method at Java Sumedang Coffee (JSC) in Genteng Village, Sukasari District, Sumedang Regency, West Java Province.Â  Primary data was collected based on test results and interviews directly with the business manager of JSC, while secondary data were obtained from published scientific articles. The results of this study show that with the use of a roasted machine for 5 hours per day or 1200 hours per year at an interest rate of 7% per year, the business of specialty roasted coffee beans production at JSC are feasible with an assumption of a minimum selling price of Rp.128,500/kg. The indicators of business feasibility are NPV (Net Present Value) Rp. 111,759,128.10; BCR (Benefit Cost Ratio) of 1.02%; IRR (Internal Rate of Return) of 6.21%; capital returned in the 17th month. While, in the coffee bean roasting service business are feasible if the minimum roasting service cost is Rp. 14,000/kg, with feasibility indicators are NPV Rp. 112,286,86; BCR of 1.23; IRR of 6.25% per month; and PBP occurred in the 17th month.